PERSAHABATAN MENURUT AJARAN AGAMA HINDU DALAM GEGURITAN DUKUH WANASARI - A.A. Pt. Suari; Gede Astrawan (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
AbstractGeguritan Dukuh Wanasari is a part of Bali Purwa literature (traditional literature) in the form of narrative poetry. Geguritan Dukuh Wanasari tells about Wayan Cita's friendship. Wayan Cita has three friends. They are I Wayan Satwa, I Made Rajas, and I Ketut Tamas who have different characters. These different characters have an impact on their friendship, especially on I Citas life. This qualitative research uses descriptive methods in explaining the results of the research. The object of the research was taken from the book Geguritan Dukuh Wanasari in 1997. It was transliterated and translated by I Made Sudiarga. The results showed that there three figures in Geguritan Dukuh Wanasari. They are Dukuh Wanasara, I Wayan Cita, I Wayan Satwa, I Made Rajas, and I Ketut Tamas. They have different characters depending on what they have learned and believe. Dukuh Wanasari and I Satwa always learn about self-improvement through literatures and religious belief. On the other hand, I Rajas and I Tamas always try to pursue temporary worldly happiness. I Cita was described as a figurewho is not very persistent and easily influenced. The friendship between I Cita and I Satwa reflects the value of satya Mitra. Their friendship has a good influence on their lives because they can control themselves and practice religious teachings well. However, the friendship of I Cita, I Rajas, and I Tamas reflects a value of mitradohaka that has a bad impact on their future and ends in death.Keywords: friendship, satya mitra, mitradohaka